Genome-Wide Scans for Delineation of Candidate Genes Regulating Seed-Protein Content in Chickpea - Upadhyaya, Hari D.; Bajaj, Deepak; Narnoliya, Laxmi; Das, Shouvik; Kumar, Vinod; Gowda, C. L. L.; Sharma, Shivali; Tyagi, Akhilesh K.; Parida, Swarup K. (Frontiers in Plant Science, 2016)
Identification of potential genes/alleles governing complex seed-protein content (SPC) trait is essential in marker-assisted breeding for quality trait improvement of chickpea. Henceforth, the present study utilized an integrated genomics-assisted breeding strategy encompassing trait association analysis, selective genotyping in traditional bi-parental mapping population and differential expression profiling for the first-time to understand the complex genetic architecture of quantitative SPC trait in chickpea. For GWAS (genome-wide association study), high-throughput genotyping information of 16376 genome-based SNPs (single nucleotide polymorphism) discovered from a structured population of 336 sequenced desi and kabuli accessions [with 150-200 kb LD (linkage disequilibrium) decay] was utilized. This led to identification of seven most effective genomic loci (genes) associated [10 to 20% with 41% combined PVE (phenotypic variation explained)] with SPC trait in chickpea. Regardless of the diverse desi and kabuli genetic backgrounds, a comparable level of association potential of the identified seven genomic loci with SPC trait was observed. Five SPC-associated genes were validated successfully in parental accessions and homozygous individuals of an intra-specific desi RIL (recombinant inbred line) mapping population (ICC 12299 x ICC 4958) by selective genotyping. The seed-specific expression, including differential up-regulation (> 4-fold) of six SPC-associated genes particularly in accessions, parents and homozygous individuals of the aforementioned mapping population with high level of contrasting seed-protein content (21-22%) was evident. Collectively, the integrated genomic approach delineated diverse naturally occurring novel functional SNP allelic variants in six potential candidate genes regulating SPC trait in chickpea. Of these, a non-synonymous SNP allele-carrying zinc finger transcription factor gene exhibiting strong association with SPC trait was found to be the most promising in chickpea. The informative functionally relevant molecular tags scaled-down essentially have potential to accelerate marker-assisted genetic improvement by developing nutritionally-rich chickpea cultivars with enhanced seed-protein content.